Improving Student Learning Outcomes on Integer Material by Using Audio-Visual Media in Grade IV SD Negeri 1 Kepahyang - Santoso, Adi (PPSDP International Journal of Education, 2024)
This study was inspired by the author’s experience as a teacher at SDN 1 Kepahyang who observed the ability of students to solve problems and their inability to distinguish between known and requested, as well as the mathematical model used in the problem, solving it, resulting in low student learning outcomes. The purpose of this study was to improve student learning outcomes on integer material by using audio-visual media in grade IV SDN 1 Kepahyang. The subjects of the study were student’s class IV with a total of 20 students (Male = 10, Female = 10) for the 2020/2021 academic year. This research was conducted on April 19 to May 3, 2021, the even semester of the 2020/2021 academic year. Based on research findings, it can be seen that student learning outcomes related to integer learning material have increased. This can be seen from the results of learning evaluations in the form of learning completeness from each cycle I (70%), and cycle II (100%). So, the use of audio-visual media in learning mathematics integer material can improve the learning outcomes of grade IV (four) students at SDN 1 Kepahyang.